Dr. Lonnie Thompson - Dr. Lonnie , Thompson (Arctic Portal, 2011)
Professor Lonnie Thompson, School of Earth Science, Ohio State University & Byrd Polar Research Center speaks here in the 6th Northern Research Forum Open Assemly, held in Iceland in September 2011. The sessions title is: Implications of the Ice Melt: A Global Overview. please click on the link above to see the video.